2016
DOI: 10.1007/s40266-016-0366-1
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Pulmonary Fibrosis and the Elderly: Diagnosis and Management Considerations

Abstract: Idiopathic pulmonary fibrosis (IPF) is a severe and progressive fibrosing interstitial lung disease, which ultimately results in respiratory failure and death. The median age at diagnosis is 66 years, and the incidence increases with age, making this a disease that predominantly affects the elderly population. IPF can often be difficult to diagnose, as its symptoms--cough, dyspnoea and fatigue--are non-specific and can often be attributed to co-morbidities such as heart failure and chronic obstructive pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 103 publications
0
41
0
Order By: Relevance
“…Our identification of FASN as a TGF-b-regulated profibrotic target has the potential to redefine the paradigm by which fibroproliferative diseases are investigated and subsequently treated. This is of particular importance for diseases such as IPF, as whereas Pirfenidone and Nintedanib are 2 recently approved therapies, both have been associated with adverse effects, two-thirds of individuals with IPF still die within 5 yr of diagnosis, and it has recently been reported that "neither Pirfenidone nor Nintedanib has a clear advantage on mortality outcomes" (65)(66)(67).…”
Section: Discussionmentioning
confidence: 99%
“…Our identification of FASN as a TGF-b-regulated profibrotic target has the potential to redefine the paradigm by which fibroproliferative diseases are investigated and subsequently treated. This is of particular importance for diseases such as IPF, as whereas Pirfenidone and Nintedanib are 2 recently approved therapies, both have been associated with adverse effects, two-thirds of individuals with IPF still die within 5 yr of diagnosis, and it has recently been reported that "neither Pirfenidone nor Nintedanib has a clear advantage on mortality outcomes" (65)(66)(67).…”
Section: Discussionmentioning
confidence: 99%
“…Smoking cessation is also important in that regard and also has implications regarding the use of long‐term oxygen therapy (LTOT). Smoking has also been shown to decrease systemic exposure to both nintedanib and pirfenidone and smoking cessation should be strongly advised when initiating either of these medications …”
Section: General Measuresmentioning
confidence: 99%
“…Smoking has also been shown to decrease systemic exposure to both nintedanib and pirfenidone and smoking cessation should be strongly advised when initiating either of these medications. 5 Depression and anxiety are other common but often overlooked co-morbidities in IPF patients, associated with a poorer quality of life and poorer outcomes. 6 Underlying depression and anxiety are often correlated with the presence of debilitating symptoms such as dyspnoea, a symptom affecting up to 90% of patients at diagnosis.…”
Section: General Measuresmentioning
confidence: 99%
“…18 Older age has been established in the literature as an IPF risk factor, but the mechanism behind aging and the development of IPF remains elusive. The median age of patients at diagnosis with IPF is 66 years.…”
Section: Discussionmentioning
confidence: 99%
“…The median age of patients at diagnosis with IPF is 66 years. 18 Older age has been established in the literature as an IPF risk factor, but the mechanism behind aging and the development of IPF remains elusive. The diagnosis and management of the disease is complicated in the elderly population where the non-specific symptoms of cough and dyspnea can be attributed to other comorbidities like heart failure and chronic obstructive pulmonary disease.…”
Section: Discussionmentioning
confidence: 99%